Pengaruh Partisipasi Cyber Army dan Perubahan Budaya Media Sosial Terhadap Keberadaan Budaya Melayu Riau - Yudi Daherman; Tessa Shasrini; Harry Setiawan (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2020)
The presence of students in Riau province has been carried away by the sophistication of social media technology, whether they are consumers or producers.Young students of social media activists are required to be creative in using it. Its presenceas a cyber army on social media has become a determining factor in the community formedin each campus based on religion. This continues to spark debate on social media whenthere is an action to defend Islam. The formation of cyber troops by naming them on socialmedia is the Muslim Cyber Army, they are tasked with escorting, filtering, and alsoclarifying news or information circulating on social media, especially on Instagram socialmedia. This study aims to determine how much influence the role of the cyber army has andchanges in social media culture on the existence of Malay Malay culture, which means thatthe old communication practices that change with new media (social media) lead tocultural changes in social media so that local culture such as Malay culture is changingRiau is affected. The results of the research under study there is a positive and significanteffect simultaneously of 54% of the role of the cyber army in changing social media cultureon the existence of Riau Malay culture. This means that students in Riau province as acyber army have a role in changing social media culture to maintain the existence of Malayculture.